Immune activation by a multigene family of lectins with variable tandem repeats in oriental river prawn (Macrobrachium nipponense). Issue 9 (16th September 2020) - Huang, Ying; Huang, Xin; Zhou, Xuming; Wang, Jialin; Zhang, Ruidong; Ma, Futong; Wang, Kaiqiang; Zhang, Zhuoxing; Dai, Xiaoling; Cao, Xueying; Zhang, Chao; Han, Keke; et al.
Abstract : Abstract : Genomic regions with repeated sequences are unstable and prone to rapid DNA diversification. However, the role of tandem repeats within the coding region is not fully characterized. Here, we have identified a new hypervariable C-type lectin gene family with different numbers of tandem repeats (Rlecs; R means repeat) in oriental river prawn ( Macrobrachium nipponense ) . Two types of repeat units (33 or 30 bp) are identified in the second exon, and the number of repeat units vary from 1 to 9. Rlecs can be classified into 15 types through phylogenetic analysis. The amino acid sequences in the same type of Rlec are highly conservative outside the repeat regions. The main differences among the Rlec types are evident in exon 5. A variable number of tandem repeats in Rlecs may be produced by slip mispairing during gene replication. Alternative splicing contributes to the multiplicity of forms in this lectin gene family, and different types of Rlecs vary in terms of tissue distribution, expression quantity and response to bacterial challenge. These variations suggest that Rlecs have functional diversity. The results of experiments on sugar binding, microbial inhibition and clearance, regulation of antimicrobial peptide gene expression and prophenoloxidase activation indicate that the function of Rlecs with the motif of YRSKDD in innate immunity is enhanced when the number of tandem repeats increases. Our results suggest that Rlecs undergo gene expansion through gene duplication and alternative splicing, which ultimately leads to functional diversity.